Preoperative MRI Evaluation of Hand Vessels in Children With Congenital Syndactyly Malformation by a Contrast-Enhanced Three-Dimensional Water-Selective Cartilage Scan - Liu, Bo; Cai, Jinhua; Tian, Xiaofei; Huang, Kaiping; Liu, Daisong; Zheng, Helin; Wang, Longlun; Yang, Jing; Xu, Hongrong (Frontiers in Pediatrics, 2022)
Background: It is crucial to preoperatively assess the arteries of the hands in congenital syndactyly malformation (CSM) patients because this information can affect the therapeutic outcome and prognosis. Objective: To investigate the value of a contrast-enhanced three-dimensional water-selective cartilage scan for the preoperative evaluation of CSM in children. Materials and Methods: Contrast-enhanced three-dimensional water-selective cartilage scan 3.0 T magnetic resonance imaging (MRI) performed in 16 clinically diagnosed CSM patients with 17 affected hands. The arteries of the hands were displayed with a focus on the bifurcation position of the common palmar digital arteries (CPDAs) and the maturity of the proper palmar digital arteries (PPDAs). The MRI results were interpreted by consensus between two experienced paediatric radiologists with ten years of MRI experience each. The MRI findings were compared with the operation results. Results: Of 51 CPDAs in the 17 affected hands, MRI showed that 30 had an abnormal bifurcation position and 20 had a normal position, and of the 102 PPDAs, 14 were shown to have an abnormal maturity and 85 a normal state, which were confirmed by surgery. The accuracy, sensitivity and specificity for determining the bifurcation position of the CPDAs based on MR maximum intensity projection reconstructed images were 98.04% (50/51), 96.77% (30/31) and 100% (20/20), respectively. The maturity of the PPDAs was judged by MR maximum intensity projection reconstructed images with an accuracy, sensitivity and specificity of 97.06% (99/102), 82.35% (14/17) and 100% (85/85), respectively. Conclusion: Contrast-enhanced three-dimensional water-selective cartilage scan has excellent performance in displaying the bifurcation position of the CPDAs and the maturity of the PPDAs and is of high value for the preoperative evaluation of CSM in children.